2016
DOI: 10.1073/pnas.1608458113
|View full text |Cite
|
Sign up to set email alerts
|

Genome engineering uncovers 54 evolutionarily conserved and testis-enriched genes that are not required for male fertility in mice

Abstract: Gene-expression analysis studies from Schultz et al. estimate that more than 2,300 genes in the mouse genome are expressed predominantly in the male germ line. As of their 2003 publication [Schultz N, Hamra FK, Garbers DL (2003) Proc Natl Acad Sci USA 100(21):12201–12206], the functions of the majority of these testis-enriched genes during spermatogenesis and fertilization were largely unknown. Since the study by Schultz et al., functional analysis of hundreds of reproductive-tract–enriched genes have been per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 41 publications
4
127
0
Order By: Relevance
“…We initially identified Tcte1 as a conserved testis-specific gene using a bioinformatic screen, as recently described (28). To determine the expression profile of Tcte1, we performed multitissue RT-PCR from adult mouse.…”
Section: Resultsmentioning
confidence: 99%
“…We initially identified Tcte1 as a conserved testis-specific gene using a bioinformatic screen, as recently described (28). To determine the expression profile of Tcte1, we performed multitissue RT-PCR from adult mouse.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, recent animal studies have shown that many testis-enriched and evolutionarily-conserved genes are not required for male fertility in mice 17 . A second hypothesis implicates leaky transcription during the massive chromatin remodeling that occurs throughout spermatogenesis 12,18,19 .…”
Section: Main Textmentioning
confidence: 99%
“…For example, by utilizing the CRISPR/Cas9 system in addition to other KO methods, >80 KO mice of genes that are predominantly expressed in the testis and conserved in both mice and humans were generated. Surprisingly, 54 of those KO male mouse lines were fertile, meaning that the importance of these genes cannot be based solely on their tissue expression profile . In contrast, there are several genes that were found to be indispensable for male fertility by using the CRISPR/Cas9 system, such as Ppp3r2 , Ccdc63 , and Cabyr .…”
Section: Crispr/cas9 and Reproductionmentioning
confidence: 99%
“…There are ~1000 genes that are predominantly expressed in the mouse testis and many of these genes still need to be analyzed with the KO approach. The genes that are essential for male fertility will be revealed more rapidly with the CRISPR/Cas9 system.…”
Section: Crispr/cas9 and Reproductionmentioning
confidence: 99%